Evaluation of the dengue surveillance system during the COVID-19 pandemic in Gunungkidul Regency in 2021 - Kamilia, Nadiyah; Utarini, Adi; Indriani, Citra (Universitas Gadjah Mada, 2022)
Purpose: The purpose of this study is to pinpoint the gaps in the Gunungkidul Regency's dengue monitoring system's implementation. Methods: Using the descriptive design. In the Gunungkidul Regency, questionnaires were used to collect primary data from the Health Office, 30 Public Health Centers, 3 Hospitals, and 1 Clinic. The d engue surveillance system assessment standard integrates the surveillance system system concept from the 2001 CDC guidelines with the attributes (Simplicity, Data Quality, Data Stability, Representation, System Acceptance, and Timeliness) and d engue surveillance system standards by directives from the Director General of Desease control of the Ministry of Health of the Republic of Indonesia in 2017. Results: Clinical criteria are used in Gunungkidul Regency to define dengue cases, whereas serological tests, such as NS-1, are rarely used there. Up to 4 (14%) of the health facilities had trouble accurately collecting reports of hospital suspicions, such as when the patient's residence was unclear and when they received treatment. According to 21 (70%) of the health centers, suspect reports were frequently collected from patients who had been admitted to hospitals outside the area. Notification letters were given to patients who had completed their treatment. The distribution of cases and the projection of an increase in instances cannot be accurately described using data from data management, as the data is not updated on a daily basis. Up to 15 health centers (50%) reported that hospital reports were frequently delayed. Conclusion: Weaknesses in the dengue surveillance system, particularly in the characteristics of simplicity, quality, data stability, and timeliness, contributed to an increase in the number of dengue cases from 2018 to 2020 in Gunungkidul Regency.